Stacking faults in silicon carbide whiskers - Choi, HJ; Lee, JG (ELSEVIER SCI LTD, 2000)
Stacking faults in SiC whiskers grown by three different growth mechanisms; vapor-solid (VS), two-stage growth (TS) and vapor-liquid-solid (VLS) mechanism in the carbothermal reduction system were investigated by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The content of stacking faults in SiC whiskers increased with decreasing the diameter of whiskers, i.e. the small diameter whiskers (<1 mu m) grown by the VS, TS and VLS mechanisms have heavy stacking faults whereas the large diameter whiskers (>2 mu m) grown by the VLS mechanism have little stacking faults. Heavy stacking faults of small diameter whiskers were probably due to the high specific lateral surface area of small diameter whiskers. (C) 1999 Elsevier Science Ltd and Techna S.r.l. All rights reserved.
Keywords: CARBOTHERMAL REDUCTION; MATRIX COMPOSITES; SIC WHISKERS; MICROSTRUCTURE; CONDUCTIVITY; NITRIDE; GROWTH